Kinetic exploration of CO2 methanation over nickel loaded on fibrous mesoporous silica nanoparticles (CHE-SM) - Muhammad Akmal, Aziz; Aishah, Abdul Jalil; Nurul Sahida, Hassan; Mahadi, Bahari; Abdul Hakim, Hatta; Tuan Amran, Abdullah; Nurfatehah Wahyu, Che Jusoh; Herma Dina, Setiabudi; Saravanan, Rajendran (Institution of Chemical Engineers, 2024)
A novel series of nickel (Ni) loaded on Fibrous Mesoporous Silica Nanoparticles (CHE-SM) support with varying Ni contents (x=1–30 wt%) were synthesized, denoted as xNi/CHE-SM and then investigated for carbon dioxide (CO2) methanation. The catalysts underwent comprehensive characterization using XRD, N2 adsorption-desorption, FESEM, FTIR-KBr, H2-TPR, and CO2-TPD techniques. The XRD and FESEM analyses confirmed the structural integrity of CHE-SM, irrespective of the Ni loading. However, the size of the nanocrystalline NiO particles appeared to be influenced by the Ni loading. Notably, 20Ni/CHE-SM exhibited the highest CO2 conversion of 92% at 350 °C, demonstrating its potential for low-temperature activation. H2-TPR and CO2-TPD results revealed favorable NiO reduction at lower temperatures, indicating medium-strength basicity that facilitated efficient CO2 and H2 adsorption and activation. Consequently, 20Ni/CHE-SM exhibited superior catalytic performance compared to other catalysts, with lower activation energy (61.5 kJ/mol). Kinetic studies focusing on 20Ni/CHE-SM indicated a molecular adsorption mechanism of CO2 and H2 on a single site after evaluation using four Langmuir-Hinshelwood models. This result was attributed to the high amount of medium strength basicity possessed by the 20Ni/CHE-SM catalyst which provided an abundance of adsorption sites, resulting in greater fractional coverage of reactants and enhancing the CH4 formation rate.